2008
DOI: 10.3174/ajnr.a1008
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Assessment of Gliomas Using11C-Methionine, [18F] Fluorodeoxyglucose, and11C-Choline Positron-Emission Tomography

Abstract: BACKGROUND AND PURPOSE:Positron-emission tomography (PET) is a useful tool in oncology. The aim of this study was to assess the metabolic activity of gliomas using 11 C-methionine (MET), [ 18 F] fluorodeoxyglucose (FDG), and 11 C-choline (CHO) PET and to explore the correlation between the metabolic activity and histopathologic features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
128
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(137 citation statements)
references
References 29 publications
5
128
1
3
Order By: Relevance
“…Positron emission tomography (PET) with administration 18 F-FDG), 11 C-methionine, 11 C-choline, or 18 F-fluoroethyl-tyrosine ( 18 F-FET) has been applied to the delineation of tumor extension, prediction of prognosis, monitoring of therapeutic effects, and diagnosis of tumor grade, although the clinical utility for these purposes remains controversial. 5,[7][8][9][10][11][12][13][14][15][16] To take advantage of PET, images from this modality have been integrated into neuronavigation for image-guided resection of gliomas. In fact, a previous report showed that complete resection of areas showing increased PET tracer uptake significantly prolonged survival among patients with high-grade glioma, whereas total resection based on MRI contrast enhancement did not.…”
Section: Introductionmentioning
confidence: 99%
“…Positron emission tomography (PET) with administration 18 F-FDG), 11 C-methionine, 11 C-choline, or 18 F-fluoroethyl-tyrosine ( 18 F-FET) has been applied to the delineation of tumor extension, prediction of prognosis, monitoring of therapeutic effects, and diagnosis of tumor grade, although the clinical utility for these purposes remains controversial. 5,[7][8][9][10][11][12][13][14][15][16] To take advantage of PET, images from this modality have been integrated into neuronavigation for image-guided resection of gliomas. In fact, a previous report showed that complete resection of areas showing increased PET tracer uptake significantly prolonged survival among patients with high-grade glioma, whereas total resection based on MRI contrast enhancement did not.…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical PET studies with FDG and MET have been conducted to discriminate among World Health Organization grades of gliomas. 4,5,7,8 Several imaging studies have demonstrated the usefulness of FDG-PET in the differentiation between low-grade and high-grade gliomas and even between grade III and grade IV gliomas. 5,7,8 Because of the associated increased glucose uptake and high rates of glycolysis, FDG-PET shows high FDG uptake in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…The uptake values of the 62 Cu-ATSM, FDG, and MET tracers were determined by assessment of the maximum standardized uptake value (SUV max ) values and T/B ratios. Dr. View version R 2.5 for LINUX (Infocom, Tokyo, Japan) software was used to merge the PET images with the MR images, 4,13,14 and each PET and MR image was volumetrically compared. To evaluate volumetric analysis, we extracted the uptake regions of the 62 Cu-ATSM images on the basis of the optimal T/B ratio thresholds of Ն1.8, a cutoff value for predicting hypoxiainducible factor-1␣ expression in our previous study.…”
Section: Image Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of MET through these mechanisms is visualized as tissue uptake on PET images, with MET being incorporated into most brain tumors, including low-grade gliomas. In general, MET uptake is lower in low-grade than in high-grade gliomas, although there is considerable overlap between these two groups, as well as between histological types [4,5]. However, several previous reports have demonstrated MET uptake in lesions associated with benign brain diseases [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
mentioning
confidence: 94%